2004
DOI: 10.1002/cpp.403
|View full text |Cite
|
Sign up to set email alerts
|

Obsessive beliefs and their relation to obsessive–compulsive symptoms

Abstract: Relationships between obsessive-compulsive symptoms and beliefs identified as relevant to obsessive-compulsive disorder (OCD) are investigated among university students and a small clinical sample. One hundred and fifty-four participants completed measures of OCD-related beliefs, OCD symptoms, and anxiety and depression symptoms. Results showed that belief domains were strongly interrelated and were not sufficiently separate to use individually in further analysis. The summed obsessive beliefs score was signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
25
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 41 publications
4
25
1
Order By: Relevance
“…However, the scores of a group of low-OCD patients did not differ from those obtained by a non-clinical control group of students. Faull, Joseph, Meaden, and Lawrence (2004), using the OBQ in a non-clinical sample and in a small OCD sample, reported that the belief domains were strongly overlapped, concluding that their consideration as independent domains is unclear. Holaway, Heimberg, and Coles (2006) reported that sub-clinical OCD and generalized anxiety disordered subjects did not differ on intolerance to uncertainty.…”
Section: Discussionmentioning
confidence: 96%
“…However, the scores of a group of low-OCD patients did not differ from those obtained by a non-clinical control group of students. Faull, Joseph, Meaden, and Lawrence (2004), using the OBQ in a non-clinical sample and in a small OCD sample, reported that the belief domains were strongly overlapped, concluding that their consideration as independent domains is unclear. Holaway, Heimberg, and Coles (2006) reported that sub-clinical OCD and generalized anxiety disordered subjects did not differ on intolerance to uncertainty.…”
Section: Discussionmentioning
confidence: 96%
“…As the present EFA generated single component structures for both the OCI-R and the OBQ-20, it is equivalent to using the total score for these scales. The use of total score may prevent redundancy (Moulding et al, 2009) since past studies have documented high correlations among the subscales for the OBQ (Woods, Tolin, & Abramowitz, 2004;Faull, Joseph, Meaden, & Lawrence, 2004). It is essential for future studies to examine the psychometric properties of these scales more carefully since most of these were not originally intended or validated for non-Western populations.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies reported different and contrasting results in exploring the relationship between OC beliefs and OCD symptoms (Belloch, Morillo & Garcia-Soriano, 2007;Sica et al, 2004;Sica, Taylor, Arrindell & Sanavio, 2006). Also, which factor structure best represents the most commonly-used measure of OC beliefs content (the Obsessive Beliefs Questionnaire; OCCWG, 2003) remains in question (see Careau, O'Connor, Turgeon, & Freeston, 2003;Dorz et al,2009;Faull, Joseph, Meaden, & Lawrence, 2004;OCCWG, 2005;Taylor, McKay, & Abramowitz, 2005).…”
Section: Introductionmentioning
confidence: 99%